UJI AKTIVITAS ANTIBAKTERI GEL EKSTRAK ETANOL DAUN ANGSANA (Pterocarpus indicus Willd.) TERHADAP BAKTERI Staphylococcus aureus - Nelly Suryani Djamain; Vivi Anggia; Nia Fachrunisa (Jurnal Insan Farmasi Indonesia, 2020)
Angsana leaves (Pterocarpus indicus Willd.) contain flavonoids, saponins, tannins, alkaloids, glycosides, triterpenoids, and steroids can be used as an active substances that formulated into antibacterial formulation gel. In this study, ethanolic extracts of Angsana leaves are formulated into gel form to optimize the antibacterial activity from the extracts. The purpose of this study belongs to determine the differences antibacterial activity of ethanolic extracts of Angsana leaves before and after being formulated into gel form. Antibacterial activity test was determined by using disc diffusion method due to Kirby-Bauer method. Based on the results, it showed that formulation contains 0.09 mg extract formed 8 mm inhibition zone and 9 mg extract without formulation formed 16 mm inhibition zone. By comparing the amount of extracts to the inhibitory zone, it is known that extract which formulated into a gel form has greater activity than extract without formulated.